The Adjunctive Treatment of Low Level Laser Therapy in Medication related Osteonecrosis of The Jaws - Revina Daniella (Sriwijaya Journal of Dentistry, 2022)
Introduction: Low level laser therapy (LLLT) is the direct application of light to stimulate responses to promote tissue healing, reduce inflammation and pain relief. It is called photobiomodulation due to anti-inflammatory properties and encourage mucosal repair. Medication related osteonecrosis of the jaws (MRONJ) represents an adverse drug reaction, consisting of progressive bone destruction in the mandible or maxilla. The treatment modality of this condition is still challenging. Methods: PubMED and Scopus were searched for published articles that have relevance to medication related osteonecrosis of the jaws and low level laser therapy. In vitro and animal studies were excluded. Eleven articles published between 2014 and 2022 were included in this review. Results: LLLT used as adjunctive therapy for MRONJ produced the improvement of pain, swelling, infection control, faster healing, repair of mucosa, bone regeneration, and prevent patient’s MRONJ stage evolution. Conclusion: The low level laser therapy used as adjunctive treatment in osteonecrosis may be considered as efficient promising option to treat MRONJ in stage II and III.